Oxytocin and mental health in college students - Veríssimo, Carolina (2019)
Mental health is the result of a combination of many factors and has a great influence on multiple aspects of the life of young adults. Some studies have found associations between oxytocin levels and quality of social relations and mental health disorders. The concern with students' mental health is increasing because most mental disorders peak during or slightly before college age. Of the mental disorders in these age groups, depression and anxiety disorders are the most frequent. Oxytocin and temperament have been emphasized as individual determinants with a biological basis. To our knowledge, there are no studies that relate oxytocin, oxytocin receptors, psychological disturbances, and temperament. We aimed to study the association between plasma oxytocin levels and two polymorphisms (SNPs), in gene receptor, mental health and temperament disturbances in university students.